2020
DOI: 10.1186/s42506-020-00041-2
|View full text |Cite
|
Sign up to set email alerts
|

Women’s enlightenment and early antenatal care initiation are determining factors for the use of eight or more antenatal visits in Benin: further analysis of the Demographic and Health Survey

Abstract: Background: Within the continuum of reproductive health care, antenatal care (ANC) provides a platform for vital health care functions, such as disease prevention, health promotion, screening, and diagnosis. It has been widely confirmed that by implementing appropriate evidence-based practices, ANC can save lives. Previous studies investigated the utilization of ANC based on the four visits model. The new guidelines set by the World Health Organization 2016 recommended increasing contacts with health providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 33 publications
8
90
1
Order By: Relevance
“…This shows that compliance with the updated recommendation is low, probably because it may not have been adopted as a national policy. This study reported a higher prevalence than a previous study conducted using Benin population-based data which also examined the coverage of eight or more ANC visits [ 36 ]. Similarly, the observed prevalence is slightly higher than results from a previous multi-country study that revealed 15.3% of mothers had eight or more antenatal contacts; with the first contact in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This shows that compliance with the updated recommendation is low, probably because it may not have been adopted as a national policy. This study reported a higher prevalence than a previous study conducted using Benin population-based data which also examined the coverage of eight or more ANC visits [ 36 ]. Similarly, the observed prevalence is slightly higher than results from a previous multi-country study that revealed 15.3% of mothers had eight or more antenatal contacts; with the first contact in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 71%
“…This underscores the importance of social and behavioural change communication to increase awareness and create demand for the use of maternal health services [12]. Similarly, the findings from previous studies showed that women enlightenment and early ANC initiation were significantly associated with eight or more ANC contacts [36,61]. There is no doubt, that early booking for ANC would result in optimal number of ANC contacts during pregnancy as those who start early will have higher possibility of achieving optimal ANC visits.…”
Section: Variablementioning
confidence: 79%
“…Decision making included women's ability to be involved in making decisions regarding; their own health; large household purchases; visits to their family and control over their earnings 5 . Re-coding to the responses was done to have two categories (1 = woman involved in decision making alone or with partner, 0 = woman not involved in decision making).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Globally, over half of maternal mortalities are due to pregnancy-related complications and over 90% of these deaths are from low and middle income countries 5 . Majority of these maternal deaths are preventable through skilled birth attendance and increased antenatal care (ANC) contacts 5 . Focused antenatal care has been shown to increase the likelihood of skilled birth attendance 1,6 and also gives health workers an opportunity to advise pregnant women on essential pregnancy care to reduce malnutrition, stillbirths, maternal mortality and morbidity, and neonatal deaths 5,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation